Ligand and copper free Sonogashira coupling to achieve 2-alkynyl d-glucal derivatives: regioselective electrophile promoted nucleophilic 5-endo-dig cyclization. Issue 43 (21st October 2015) - Shamim, Anwar; Vasconcelos, Stanley N.S.; Ali, Bakhat; Madureira, Lucas Sousa; Zukerman-Schpector, J.; Stefani, Hélio A.
Graphical abstract: Abstract: A general approach for the synthesis of 2-alkynyl-d -glucal derivatives has been achieved through a ligand and copper-free Sonogashira coupling of 2-iodo-3, 4, 6-tri- O -acetyl-d -glucal and terminal alkynes using palladium acetate in DMF at room temperature with very good to excellent yields. The scope of this reaction is shown by regioselective electrophile promoted nucleophilic (EPN) 5- endo -dig cyclization of these alkynyl-d -glucal derivatives using gold(III) chloride in 1, 4-dioxane at reflux.